Academic Major Satisfaction as A Predictor of Psychological Well-Being and Psychological Distress - Wening Cahyawulan; Bella Yugi Fazny; Karsih Karsih (Universitas Ahmad Dahlan, 2022)
This study examined the relationship between academic major satisfaction and students’ psychological well-being and distress. Data were collected from 429 Indonesian university students (17-24 years of age) using a purposive sampling technique. Data were collected using an academic major satisfaction scale, brief symptom inventory, and Ryff’s psychological well-being adapted to the Indonesian context. The data were analyzed using descriptive analysis and Mann Whitney U-test. The result showed that students with higher major satisfaction exhibited higher psychological well-being and lower psychological distress. This paper also discusses the importance of providing individual planning services by school counselors to help students find the most suitable major for them.